2017
DOI: 10.1093/pcp/pcx158
|View full text |Cite
|
Sign up to set email alerts
|

The MADS-Box Gene SlMBP21 Regulates Sepal Size Mediated by Ethylene and Auxin in Tomato

Abstract: Normal organ size is achieved by successful co-ordination of cell proliferation and cell expansion, which are modulated by multiple factors such as ethylene and auxin. In our work, SlMBP21-RNAi (RNA interference) tomato exhibited longer sepals and improved fruit set. Histological analysis indicated that longer sepals were attributed to cell expansion. To explore how SlMBP21 regulates sepal size, we compared the transcriptomes of sepals between SlMBP21-RNAi and the wild type by RNA sequencing and found that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 62 publications
1
24
0
Order By: Relevance
“…Among the green parts of the flower, sepal has the greatest ability to photosynthesis, follow by the receptacle [3]. The contents of Chl and the activity of ribulose-1, 5-bisphosphate carboxylase/oxygenase, the key photosynthetic enzyme, are both increased in longer sepals, and photosynthesis is enhanced in longer sepals, which may contribute by improving the fruit set [2]. Conclusively, sepal morphology is closely associated with fruit development.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…Among the green parts of the flower, sepal has the greatest ability to photosynthesis, follow by the receptacle [3]. The contents of Chl and the activity of ribulose-1, 5-bisphosphate carboxylase/oxygenase, the key photosynthetic enzyme, are both increased in longer sepals, and photosynthesis is enhanced in longer sepals, which may contribute by improving the fruit set [2]. Conclusively, sepal morphology is closely associated with fruit development.…”
Section: Introductionmentioning
confidence: 93%
“…The larger sepal size tightly associates with the protection of flower whorl and better fruit quality [1]. In SlMBP21-RNAi tomato, the sepals are longer and fruit sets are improved [2]. Among the green parts of the flower, sepal has the greatest ability to photosynthesis, follow by the receptacle [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, TM8 overexpression in tomato plants generated anomalous stamens with poorly viable pollen ( Daminato et al, 2014 ). A recent study suggested the tomato MADS-box gene SlMBP21 is a novel factor involved in organ size control ( Li et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%